Образна основа фразеологічних одиниць та проблема їх мовно- культурної реконструкції - Жуйкова, Маргарита (Видавництво Львівської політехніки, 2015)
The article shows that on the phraseological level the internal form of an idiom, which is made up by the lexical meanings of its components, and the figurative base, which serves as the basis for the idiomatic meaning, should be distinguished. The internal form, figurative motivation and semantics of the idioms with a component горіх (orzech) in Ukrainian, Byelorussian, Russian and Polish are analyzed.
Keywords: фразеологічне значення; ідіома; внутрішня форма; образна основа; мотивація; мовно-культурна реконструкція